Development Of Longitudinal Water Turbine For Waterfall - Dr Sofian Bin Mohd ,; MOHD FAZIL, MUHAMAD ZAIM; Sofian Mohd, (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Spiral water turbines are a type of water turbine that uses the spiral motion of water to generate electricity. They are a promising alternative to traditional water turbines, as they can be used in a wider range of conditions and are more efficient. This study investigates the fabrication and performance of a spiral water turbine. The turbine was fabricated using 3D printing technology, and its power, torque, and angular velocity were evaluated under different flow condition. The results of the study show that the spiral water turbine is a promising technology for generating electricity from water. The turbine was able to generate a significant amount of power, even at low flow rates. The torque and angular velocity of the turbine were also found to be comparable to those of traditional water turbines. The findings of this study suggest that spiral water turbines could be a viable option for small-scale hydropower generation. Further research is needed to optimize the design of spiral water turbines and to assess their long-term performance.